The influence of management creativity on the optimality of management decisions over time: An innovative aspect - Pavlenchyk, Nataliia; Pavlenchyk, Anatolii; Skrynkovskyy, Ruslan; Tsyuh, Svyatoslav (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
The study aimed at establishing the close relationship between the creativity of managers and the time spent making managerial decisions at the enterprise level. A linear least squares regression model determined the coefficient of dependence of time spent on management decision-making and creativity. The research used a quantitative approach and a sociological survey of heads and managers of enterprises of various sizes and organizational and legal forms. The authors compiled models of the formation of creative management in the enterprise based on motivational factors and the process of forming management decisions on the basis of management creativity. In the study, and for the first time, a scale of the creativity level and a scale of managers’ motivation were proposed. The results of conducted sociological research and the use of the regression model of the factors taken into account show that the average level of creativity of managers involved in decision-making and their motivation coefficient has the greatest Influence on the time spent on managerial decisions. The research has theoretical and practical significance, and managers can use its results in practice to save time and improve the efficiency of management decision-making and staff motivation.